ADVANCED TECHNIQUES IN MULTI-LABEL TEXT CLASSIFICATION: INTEGRATION OF BETA ANT COLONY AND DEEP LEARNING APPROACHES - Shrivastava, Amit; Rakesh Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The rapid growth of unstructured textual data in various domains has necessitated the development of sophisticated techniques for multi-label text classification. Traditional methods often struggle with handling the complexity and interdependence of multiple labels, leading to suboptimal performance. This paper presents an advanced approach that integrates the Beta Ant Colony Optimization (BACO) algorithm with deep learning techniques for multi-label text classification. The BACO algorithm effectively explores the feature space and selects relevant features by leveraging pheromone trails, while the deep learning model captures intricate patterns and relationships within the textual data. The integration of these two methodologies aims to enhance the efficiency and accuracy of multi-label classification tasks, particularly in domains where label dependency is prominent. Empirical evaluations on benchmark datasets demonstrate that the proposed hybrid approach outperforms existing state-of-the-art techniques in terms of precision, recall, F1-score, and computational efficiency. The findings suggest that combining heuristic optimization algorithms with deep learning can significantly improve multi-label text classification performance, providing a robust solution for real-world applications.